Wisata Alam Gunung Latimojong di Dusun Karangan Kabupaten Enrekang - Muh. Abdah Al-Adien; Aris Alimuddin; Juhana Said (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2026)
Mount Latimojong, located in Karangan Hamlet, Enrekang Regency, is one of the leading natural tourism destinations in South Sulawesi with its potential for beautiful mountain panoramas, biodiversity, and local cultural values. This study aims to identify the natural tourism potential of Mount Latimojong, analyze the supporting and inhibiting factors for its development, and formulate a sustainable management strategy. The research method used is a qualitative descriptive approach with data collection techniques through field observations, in-depth interviews with the community and managers, and documentation studies. The results show that Mount Latimojong has a main attraction in the form of a hiking trail to the highest peak in Sulawesi, a diversity of endemic flora and fauna, and pristine natural panoramas. Supporting factors for development include improving accessibility and high interest from special interest tourists, while inhibiting factors include limited supporting facilities and a lack of targeted promotion. The conclusion of this study is that the development of Mount Latimojong natural tourism requires synergy between the government, the community, and the private sector with a focus on environmental conservation and strengthening tourism infrastructure.